Rediseño del programa de tecnovigilancia de la Clínica Visual y Auditiva del Instituto para Niños Ciegos y Sordos del Valle del Cauca (2018)
Technosurveillance seeks mainly to guarantee the safety of patients, users and collaborators by mitigating the effects of adverse events and/or incidents, therefore the objective of the practice proposes to redesign the Technosurveillance program of the Visual and Auditory Clinic of the Institute for Blind and Deaf Children (INCS) of Valle del Cauca, according to what is established in resolution 4816 of 2008. The analysis was carried out in a general way for the entire Clinic, including besides the offices of Cali, Buenaventura and Palmira. It began with the current diagnosis of the Technosurveillance Program, to then establish the appropriate adjustments according to the current regulations; Subsequently, a methodology was proposed for the identification, evaluation and control of the risks associated with the use of the main biomedical equipment of the institution, ending with the establishment of assertive disclosure mechanisms. Among the main results, from the identified faults corrective actions were raised with the team, finding improvement actions, where 85.3% of the respondents understood the program's disclosure, and 41.17% gave a grade of 4 to the program, which is positive for the initial purpose